Self Assessment (Kunci Keberhasilan Mahasiswa Calon Guru Dalam Menganalisis Konsep) - Tamaela, Elsina S.; Sopacua, Venty (INSTITUT AGAMA ISLAM NEGERI AMBON, 2020)
Self assessment is one form of assessment that can improve student learning outcomes. This research is a descriptive study that aims to describe in detail the achievement of competencies of prospective physics teacher students in analyzing concepts. The population in this study were physics education students and the samples were those who offered physics studies courses with a total of 30 students. Data collection was carried out for two months in a physics material study class. The research data will then be processed descriptively according to the research needs. The results showed that self-assessment was able to improve the ability of students to analyze concepts. This happens because self-assessment gives space to students to assess their abilities; know their strengths and weaknesses in analyzing concepts; find the root of their failure. Besides that model self assessment is a tool for students to communicate with lecturers to find solutions to their failures. Thus it can be concluded that self assessment is able to improve the competency of prospective physics teacher students in analyzing concepts well.